2020
DOI: 10.1289/ehp7124
|View full text |Cite
|
Sign up to set email alerts
|

Boiled or Bottled: Regional and Seasonal Exposures to Drinking Water Contamination and Household Air Pollution in Rural China

Abstract: Background: Inadequate access to safe drinking water remains a global health problem, particularly in rural areas. Boiling is the most commonly used form of point-of-use household water treatment (HWT) globally, although the use of bottled water in low- and middle-income countries (LMICs) is increasing rapidly. Objectives: We assessed the regional and seasonal prevalence of HWT practices (including bottled water use) in low-income rural areas in two Chinese provinces, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 48 publications
1
21
0
2
Order By: Relevance
“…Since there is a lack of access to clean drinking water, boiling water is the most common method for water treatment, especially in rural areas ( 14 ). The findings from a national survey revealed that over 85% of households in rural China regularly drink boiled water ( 12 ). However, a previous study found that there was no significant association between boiled water and the biomarkers of health, including eosinophilia, anemia, and obesity ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there is a lack of access to clean drinking water, boiling water is the most common method for water treatment, especially in rural areas ( 14 ). The findings from a national survey revealed that over 85% of households in rural China regularly drink boiled water ( 12 ). However, a previous study found that there was no significant association between boiled water and the biomarkers of health, including eosinophilia, anemia, and obesity ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the quality of drinking water has been considerably improved due to the efforts of governments. For example, a large amount of capital has been spent to improve drinking water treatment and supply infrastructure in the last few decades in China ( 12 ). The main source of drinking water has changed from unimproved water, such as wells, rivers, and lakes, to improved water.…”
Section: Introductionmentioning
confidence: 99%
“…This is noteworthy when one considers that in 2013, China surpassed the USA to become the world's largest market for bottled water by volume [15]. Furthermore, limited available data indicate that even in rural China more and more households are turning to bottled water (19 l bottles) as their primary source of drinking water [16,17].…”
Section: Background and Justificationmentioning
confidence: 99%
“…A study recently published in Environmental Health Perspectives explored these questions in rural Chinese communities. 2 …”
mentioning
confidence: 99%
“…A study recently published in Environmental Health Perspectives explored these questions in rural Chinese communities. 2 Looking at a representative cross section of households in 15 villages each in Guangxi and Henan Provinces, the authors of the new study collected a variety of data around water sources, sanitation, health, and gender equity. They measured thermotolerant coliforms (TTCs) in samples of drinking water as an indicator of fecal contamination.…”
mentioning
confidence: 99%